Pendidikan Islam dalam Dinamika Gerakan Islam Kontemporer: Rekonstruksi Pendidikan Pesantren dan Neo-Modernis - Hadi, Muhammad Syamsul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2015)
The paper highlights the concept for the development and implementation ofintegrative educational boarding school as an attempt to erode dichotomousdualistic in the world of Islamic education in Indonesia. Specifically this paperexamines how the concepts of Neo-modernism is like in the reconstructionof Islamic education as an effort to develop Islamic education, as well as theimplications and applications of the concept in the reconstruction of schools andintegrative education in the context of Indonesia (by taking the focus of Islamicboarding schools) and the development of integrative educational concept in thedevelopment of learning and Islamic education curriculum.